Creation and modulation of conductivity in laser-irradiated SrTiO3 single crystals. (November 2018) - Zhang, Z.T.; Yan, H.; Wang, S.H.; Ren, L.X.; Chen, C.L.; Jin, K.X.
Abstract: We realize a controllable metallic behavior on stoichiometric (100) SrTiO3 single crystals via KrF laser irradiation, which strongly depends on vacuum and laser energy density. Moreover, this metallic conduction is caused by oxygen deficiency and can be manipulated by light illumination and electrostatic gating field. The laser-irradiated SrTiO3 shows sensitive persistent photoresponse with a relative change in the resistance of about 45% at 20 K for a 360 nm light. In addition, the conduction can also be modulated to a lower (higher) state by a positive (negative) backgate. Our results highlight the possibility of tuning the electrical properties of oxides. Graphical abstract: Unlabelled Image